Retardation of the Calvin Cycle Contributes to the Reduced CO2 Assimilation Ability of Rice Stripe Virus-Infected N. benthamiana and Suppresses Viral Infection - Bi, Ji’an; Yang, Yong; Chen, Binghua; Zhao, Jinping; Chen, Zhuo; Song, Baoan; Chen, Jianping; Yan, Fei (Frontiers in Microbiology, 2019)
Rice stripe virus (RSV) is naturally transmitted by the small brown planthopper and infects plants of the family Poaceae. Under laboratory conditions, RSV can infect Nicotiana benthamiana by mechanical inoculation, providing a useful system to study RSV-plant interactions. Measurements of CO2 assimilation ability and PSII photochemical efficiency showed that these were both reduced in N. benthamiana plants infected by RSV. These plants also had decreased expression of the N. benthamiana Phosphoribulokinases (NbPRKs), the key gene in the Calvin cycle. When the NbPRKs were silenced using the TRV-Virus Induced Gene Silencing system, the plant showed the decreased CO2 assimilation ability, indicating that the down-regulated expression of NbPRKs contributes to the reduced CO2 assimilation ability of RSV-infected plant. Additionally, NbPRKs-silenced plants were more resistant to RSV. Similarly, resistance was enhanced by silencing of either NbRbCS or NbPGK, two other key genes in the Calvin cycle. Conversely, transgenic plants overexpressing NbPRK1 were more susceptible to RSV infection. The results suggest that a normally functional Calvin cycle may be necessary for RSV infection of N. benthamiana.